2011
DOI: 10.14310/horm.2002.1325
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid carcinoma in multiple endocrine neoplasia type 1. Case report and review of the literature

Abstract: Parathyroid carcinoma is an infrequent cause of primary hyperparathyroidism. Although hyperparathyroidism in multiple endocrine neoplasia 1 (MEN1) syndrome is the most common manifestation, parathyroid carcinoma is rare. We report a male patient who was diagnosed at 44 years of age with parathyroid carcinoma in the context of MEN1 syndrome coincident with a malignant gastrinoma and non-functioning adrenal adenomas. A genetic analysis revealed the mutation W183c in exon 3 of the MEN1 gene. the diagnosis of carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 22 publications
1
33
0
9
Order By: Relevance
“…On the one hand, some studies indicate that 10-15% of parathyroid adenomas in patients with HPT-JT progress to cancer. On the other hand, somatic gene mutations of HRPT2/CDC73 are present in 66-100% of sporadic parathyroid carcinomas and occur sparsely in adenomas [17,[23][24][25]. Moreover, Svedlund et al [26] reported that EZH2 gene amplification (an oncogene, the histone 3 lysine 27 methyltransferase) is a genetic aberration common to parathyroid tumours.…”
Section: Aetiology Of Parathyroid Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, some studies indicate that 10-15% of parathyroid adenomas in patients with HPT-JT progress to cancer. On the other hand, somatic gene mutations of HRPT2/CDC73 are present in 66-100% of sporadic parathyroid carcinomas and occur sparsely in adenomas [17,[23][24][25]. Moreover, Svedlund et al [26] reported that EZH2 gene amplification (an oncogene, the histone 3 lysine 27 methyltransferase) is a genetic aberration common to parathyroid tumours.…”
Section: Aetiology Of Parathyroid Cancermentioning
confidence: 99%
“…MEN 1 syndrome is associated with germline MEN1 tumour suppressor gene mutation and includes the combination of neoplasms located most commonly in the parathyroid glands, the anterior pituitary gland, and the pancreas [24,27]. In the classic forms of MEN 1, hyperparathyroidism is usually the earliest clinical presentation [28].…”
Section: Aetiology Of Parathyroid Cancermentioning
confidence: 99%
See 3 more Smart Citations